2022
DOI: 10.1108/tqm-09-2021-0281
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual framework of quality cost chain in strategic cost management

Abstract: PurposeThis study aims to discover a practical and effective way to apply the quality cost concept in Strategic Cost Management (SCM) framework. The interaction of preventive, appraisal and failure (PAF) activities in a company's internal value chain will be the starting point of SCM implementation.Design/methodology/approachThis study begins by establishing value chain and quality costs as the scope of conceptual analysis. Discussions on the interrelationships between activities, quality and costs were gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Even that is not as fast as the practice of its implementation. In recent years, the application of managerial accounting indicated that commercial businesses would heavily rely on strategic management accounting to be competitive by remaining inventive, advancing, and combining methods in accounting processes (Kalifa et al, 2020;Li, 2018;Oyewo, 2021;Tambunan, 2022). The results of other studies show that rapid technological changes are one of the environmental factors that significantly affect a company's internal processes, including the management accounting system (MAS) (Ghasemi et al, 2019) and accounting process in general (Marrone & Hazelton, 2019), reporting and auditing (Lombardi & Secundo, 2021;Marrone & Hazelton, 2019).…”
Section: Figure 2 Managerial Accounting On Bibliographic Study In Asi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Even that is not as fast as the practice of its implementation. In recent years, the application of managerial accounting indicated that commercial businesses would heavily rely on strategic management accounting to be competitive by remaining inventive, advancing, and combining methods in accounting processes (Kalifa et al, 2020;Li, 2018;Oyewo, 2021;Tambunan, 2022). The results of other studies show that rapid technological changes are one of the environmental factors that significantly affect a company's internal processes, including the management accounting system (MAS) (Ghasemi et al, 2019) and accounting process in general (Marrone & Hazelton, 2019), reporting and auditing (Lombardi & Secundo, 2021;Marrone & Hazelton, 2019).…”
Section: Figure 2 Managerial Accounting On Bibliographic Study In Asi...mentioning
confidence: 99%
“…From a conceptual and application standpoint, managerial accounting has periodically undergone various developments (Bromwich & Scapens, 2016;Hesford et al, 2006;Kumar et al, 2020a;Oyewo, 2021;Tambunan, 2022). The object of its application is no longer at the product or department level but across departments and even becomes part of a strategic value chain analysis (Li, 2018;Shank, 1989;Wang, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…ISM analysis is used to determine the priority among quality costs. The PAF quality cost model can be applied, then treated as performance indicators for each activity (Tambunan, 2022). This approach is intended to address the complexities of strategic quality management.…”
Section: Introductionmentioning
confidence: 99%